From glissile to sessile: Effect of temperature on 〈110〉 dislocations in perovskite materials. (15th July 2016) - Hirel, Pierre; Carrez, Philippe; Cordier, Patrick
Abstract: In perovskite-type strontium titanate (SrTiO3 ) 〈110〉 dislocations, which are the main carriers of plastic flow at low temperature, lose their mobility as temperature increases, leading to brittle failure above 1050 K. We present theoretical evidence for a change in their core structure into a sessile, climb-dissociated configuration at high temperature. This mechanism is shown to operate in both SrTiO3 and MgSiO3, indicating that it may be a general feature of perovskite-type materials. It follows that the activity of the 〈110〉 slip system depends critically on the strain rate-temperature couple, ε ̇ T . Graphical abstract: